DNA and RNA vaccines against tuberculosis: a scoping review of human and animal studies - Kazakova, Alisa; Zhelnov, Pavel; Sidorov, Roman; Rogova, Anna; Vasileva, Olga; Ivanov, Roman; Reshetnikov, Vasiliy; Muslimov, Albert (Frontiers in Immunology, 2024)
To comprehensively identify and provide an overview of in vivo or clinical studies of nucleic acids (NA)-based vaccines against TB we included human or animal studies of NA vaccines for the prevention or treatment of TB and excluded in vitro or in silico research, studies of microorganisms other than M. tuberculosis, reviews, letters, and low-yield reports. We searched PubMed, Scopus, Embase, selected Web of Science and ProQuest databases, Google Scholar, eLIBRARY.RU, PROSPERO, OSF Registries, Cochrane CENTRAL, EU Clinical Trials Register, clinicaltrials.gov, and others through WHO International Clinical Trials Registry Platform Search Portal, AVMA and CABI databases, bioRxiv, medRxiv, and others through OSF Preprint Archive Search. We searched the same sources and Google for vaccine names (GX-70) and scanned reviews for references. Data on antigenic composition, delivery systems, adjuvants, and vaccine efficacy were charted and summarized descriptively. A total of 18,157 records were identified, of which 968 were assessed for eligibility. No clinical studies were identified. 365 reports of 345 animal studies were included in the review. 342 (99.1%) studies involved DNA vaccines, and the remaining three focused on mRNA vaccines. 285 (82.6%) studies used single-antigen vaccines, while 48 (13.9%) used multiple antigens or combinations with adjuvants. Only 12 (3.5%) studies involved multiepitope vaccines. The most frequently used antigens were immunodominant secretory antigens (Ag85A, Ag85B, ESAT6), heat shock proteins, and cell wall proteins. Most studies delivered naked plasmid DNA intramuscularly without additional adjuvants. Only 4 of 17 studies comparing NA vaccines to BCG after M. tuberculosis challenge demonstrated superior protection in terms of bacterial load reduction. Some vaccine variants showed better efficacy compared to BCG.